Battle royale - Pallotta, Jerry (New York Scholastic, Inc., 2018)
Which dangerous animals would win in a fight? Find out in this awesome bind-up of five books in the popular Who Would Win? series. The collection features a range of mammals, sea creatures, reptiles, and dinosaurs to satisfy all kinds of animal fans.
Who would win? --Killer whale vs. great white shark --Rhino vs. hippo --Tyrannosaurus rex vs. velociraptor --Wolverine vs. Tasmanian devil --Alligator vs. python --Who has the advantage?
Consists of material previously published between 2009 and 2014.
5 books in 1!"--Cover.
Appeals to: 1st-3rd graders